PENGARUH EKSPOR DAN IMPOR TERHADAP POSISI CADANGAN DEVISA INDONESIA PERIODE 1991-2015 - NURO IRAWATI; Ahmad Zafrullah TN.; Sugeng Hariadi (CALYPTRA, 2018)
Foreign exchange reserves can be an important indicator to see how far the country can trade internationally and to show the strong weakness of a country's economic fundamentals. The size of foreign exchange reserves is influenced by several factors, one of which is export and import activities. This study aims to identify the effect of exports and imports on the position of Indonesia's foreign exchange reserves. The object used in this study is the Indonesian state with a period of 25 years from 1991 to 2015. This study uses a quantitative approach with the Vector Autoregression method (VAR) using Eviews 9. The findings of research results show that the current foreign exchange reserves are influenced by foreign exchange reserves one year ago positively, exports one year ago negatively, imports one year ago positively, exports two years ago positively, imports two years ago negatively. Exports and imports may affect Indonesia's foreign exchange reserves in accordance with the theory that export exports have a significant positive effect and imports have significantly negative impact on new foreign exchange reserves will be seen in the next two years.